Seasonal changes in free 25-(OH)D and vitamin D metabolite ratios and their relationship with psychophysical stress markers in male professional football players - Ksiaze, A.; Zagrodna, A.; Lombardi, G.; Slowinska-Lisowska, M. (Frontiers in Physiology, 2023)
Introduction: Novel markers of vitamin D status are currently being investigated, including free 25-(OH)D (25-(OH)DF) and the vitamin D metabolite ratio (24,25-(OH)2D3:25-(OH)D3; VMR). The VMR may provide additional functional information on vitamin D metabolism in athletes. Therefore, the main objective of the current study was to evaluate 25-(OH)DF, bioavailable 25-(OH)D (25-(OH)DB), VMR, and psychophysical stress markers during different training periods over a half-season. The second aim was to assess the association between vitamin D binding protein (VDBP), total and free 25-(OH)D, VMRs, and psychophysical stress markers in professional football players. Moreover, we examined the relationship between 25-(OH)D3 and vitamin D metabolites (24,25-(OH)2D3, 3-epi-25-(OH)D3) to determine if training loads in different training periods influenced the vitamin D metabolome.